Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.4300/jgme-d-15-00273.1
|View full text |Cite
|
Sign up to set email alerts
|

Improving Residents' Safe Opioid Prescribing for Chronic Pain Using an Objective Structured Clinical Examination

Abstract: Background Internal medicine residents care for a sizable number of patients with chronic pain. Programs need educational strategies to promote safe opioid prescribing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 29 publications
(29 reference statements)
0
30
0
Order By: Relevance
“…Although patients with cancer—especially those receiving palliative care or hospice care—often are exempt from more stringent authorization requirements, these requirements nonetheless create a trickle‐down effect of increasing paperwork and phone calls to speak to a representative and explain the clinical justification for the prescribed opioid in a patient with cancer. Finally, although there is a movement to teach physicians‐in‐training how to manage pain, educational initiatives often focus on identifying aberrant drug‐seeking behaviors and understanding the management of nonmalignant pain . This is quite different from teaching physicians how to safely and effectively use opioids to manage pain secondary to active malignant disease.…”
Section: Barriers To Adequate Pain Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Although patients with cancer—especially those receiving palliative care or hospice care—often are exempt from more stringent authorization requirements, these requirements nonetheless create a trickle‐down effect of increasing paperwork and phone calls to speak to a representative and explain the clinical justification for the prescribed opioid in a patient with cancer. Finally, although there is a movement to teach physicians‐in‐training how to manage pain, educational initiatives often focus on identifying aberrant drug‐seeking behaviors and understanding the management of nonmalignant pain . This is quite different from teaching physicians how to safely and effectively use opioids to manage pain secondary to active malignant disease.…”
Section: Barriers To Adequate Pain Managementmentioning
confidence: 99%
“…Finally, although there is a movement to teach physicians-in-training how to manage pain, educational initiatives often focus on identifying aberrant drug-seeking behaviors and understanding the management of nonmalignant pain. 32 This is quite different from teaching physicians how to safely and effectively use opioids to manage pain secondary to active malignant disease.…”
Section: System and Regulatory Barriersmentioning
confidence: 99%
“…11 Recent studies demonstrated the use of skills-based and simulated learning to reinforce content taught via direct instruction. [12][13] This study expands this by assessing the impact of an opioid tapering curriculum on the following primary endpoints: the number of patients on chronic opioid therapy (COT), average morphine equivalent daily (MED) per patient, percentage of patients on >50 MED and >90 MED, and number of patients on concomitant benzodiazepines.…”
Section: Reportsmentioning
confidence: 99%
“…915 Four of these educational interventions are skills based, 10,1315 three are case based, 9,11,12 and one focuses on faculty development regarding teaching residents in the primary care clinic. 13 These publications demonstrate that education can improve residents' attitudes, 14 knowledge, 10,15 and confidence 10 in regard to safe opioid prescribing. However, to our knowledge, there have been no publications to date in MedEdPORTAL focusing on the interface between chronic pain and opioid use disorder or reporting actual improved patient-level outcomes in addition to improved educational results.…”
Section: Introductionmentioning
confidence: 99%